Remember, if you add negative four, you're really subtracting four, or if you take away negative four, you're really adding four.
-n+(-4)-(-4n)+6
-n-4+4n+6 simplify
{-n+4n are like terms, so combine them. -n+4n is exactly the same as 4n-n, so flip them around if it helps. Just remember to keep the sign with the right number. Same thing with -4+6.}
Answer:
3n+2
Answer:
b
Step-by-step explanation:
i dont really know how to explain my proccess clearly to you, but i got it right on one of my quizes
<span>3x^2−2x+7=0
</span>3x^2−2x+1/3+7−1/3=<span>0
</span><span>3<span>(x^2−2x/3+1/9)</span>+7−1/3=0
</span><span>3<span><span>(x−1/3)^</span>2</span>+(21−1)/3=0
</span><span>3<span><span>(<span>x−1/3</span>)^</span>2</span>=−<span>20/3
</span></span><span><span>(<span>x−<span>1/3</span></span>)^</span>2</span>=−<span>20/9</span>
The number of jolly rangers candy she has is 22. The number of twix bars she has is 11.
<h3>What are the linear equations that represent this question?</h3>
j + t = 33 equation 1
4t = 2j
j = 2t equation 2
Where:
j = number of jolly rangers
t = j = number of twix
<h3>How many twix candies does Julianna have?</h3>
Substitute for j in equation 1 using equation 2
2t + t = 33
3t = 33
t = 11
<h3>How many jolly candies does Julianna have?</h3>
Subsitute for t in equation 2
j = 11 x 2 = 33
To learn more about simultaneous equations, please check: brainly.com/question/25875552
#SPJ1